(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Each poet has his own style, which can be revealed only on the basis of artistic analysis. This article is dedicated to revealing the poetic skills of the creator based on the artistic analysis of Muhammad Yusuf’s poems. The poet’s poetic discoveries, language features of his poetry, subject and composition are highlighted.